Uji Validitas dan Reliabilitas Alat Tes Penalaran Numerik untuk Penjurusan Siswa SMA di Jakarta - Yusin Liauw; Christiany Suwartono (Jurnal Ilmiah Psikologi MIND SET, 2011)
The aim of this study was to examine the validity and reliability of Numerical Reasoning Test which measures numerical reasoning. Data (N=422) was taken from 13 high schools in Jakarta. Data consist of scores from high school students. The results showed that Numerical Reasoning Test had significant correlations with IST RA and TKD 1-R which measures numerical reasoning and reading comprehension. Criterion validity analysis showed that Numerical Reasoning Test was unable to predict summary report for high schools students. Reliability analysis showed that Numerical Reasoning Test was consistent measuring numerical reasoning.